6-Bromo-1H-Indazole Bearing 1,2,3-Triazole Analogues: Synthesis, Characterization and Antimicrobial Evaluation (Journal of Scientific Research, 2025)
This research paper covers the synthesis of novel pharmaceutically active and high yield scaffolds with easier pathway. A series of novel 1,2,3-traizole derivatives tethered with 6-bromo-1H-indazole were synthesized using various 2-azido-N-arylacetamide derivatives via 1,3-dipolar cycloaddition reaction. Structural evaluation was carried out using different analytical techniques such as IR, Mass and 1H-NMR spectroscopy. Further, newly synthesized molecules were evaluated for their antimicrobial efficacy using different bacterial and fungal strains. Several of these synthesized derivatives expressed moderate to good inhibition in comparison with standard drugs.